2021
DOI: 10.2337/figshare.14618409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone Mineral Density and Type 1 Diabetes in Children and Adolescents: A Meta-analysis

Abstract: <u>Background</u> <p>There is substantial evidence that adults with type 1 diabetes have reduced bone mineral density (BMD), however findings in youth are inconsistent.</p> <p><u>Purpose</u></p> <p>Systematic review and meta-analysis of BMD in youth with type 1 diabetes using multiple modalities: dual energy X-ray absorptiometry (DXA), peripheral quantitative computed tomography (pQCT) and/or quantitative ultrasound (QUS).</p> <p><u>Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…Multiple studies have examined bone parameters in children with T1D by DXA and have reported normal 22–26 or low lumbar spine BMD, 10,12–17,19,20 but these studies had heterogeneous study populations, limiting direct comparison between them, as highlighted in our recent systematic review 2 . Our study cohort had lower right femoral neck BMD similar to previous studies in young adults 15,23,25 .…”
Section: Discussionsupporting
confidence: 55%
“…Multiple studies have examined bone parameters in children with T1D by DXA and have reported normal 22–26 or low lumbar spine BMD, 10,12–17,19,20 but these studies had heterogeneous study populations, limiting direct comparison between them, as highlighted in our recent systematic review 2 . Our study cohort had lower right femoral neck BMD similar to previous studies in young adults 15,23,25 .…”
Section: Discussionsupporting
confidence: 55%
“…The literature on DXA measurements to assess bone mass in children and adolescents with T1DM is conflicting. The most recent, comprehensive meta-analysis including 2,617 children with T1DM showed significantly lower mean total body BMD, lumbar spine BMD, and femur neck BMD (−0.04 kg/cm 2 , −0.02 g/cm 2 and −0.04 g/cm 2 , respectively) compared to 3,851 healthy controls [27]. Some smaller cross-sectional studies in children with T1DM revealed lower total body BMD Z -scores compared to controls [34], lower total body less head (TBLH) BMC and aBMC at the femoral neck, lower tibial cortical vBMD [35], lower total body, and lumbar spine BMC [36] when compared to age-matched reference data.…”
Section: Dxa-related Bone Health Results In Children With T1dm the Ro...mentioning
confidence: 99%
“…Further evidence for the impact of overall health on bone health is provided by a study by Pham-Short et al [24], which showed lower BMC at the radius measured by pQCT in children with T1DM and well-controlled celiac disease compared to children with T1DM without celiac disease. Finally, a recent comprehensive meta-analysis showed that the mean differences in tibial trabecular vBMD and radial trabecular vBMD (−11.32 kg/cm 3 and −0.91 g/cm 3 , respectively) were significantly lower in youth with T1DM compared to controls [27].…”
Section: Outcomes Of Bone Geometry and Microarchitecture By Pqct Hrpq...mentioning
confidence: 99%
See 2 more Smart Citations